Identification of Academic and Professional English Language Needs for Health Students at Hafshawati University - Siti Aisyah Syaiful Arifin; Raudhatul Islam; Lilik Rohmatul Amelia; Moh. Jibrail El-Furqon; Abdul Hanan (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
English language skills are an essential competency for health students, especially in accessing scientific literature, understanding medical terminology, and facing the demands of professional globalization. However, the suitability of the English language learning curriculum with the specific needs of health students is still an issue. This study aims to identify the academic and professional English language needs of health students at Hafshawati University. The study used a qualitative approach with an open-ended questionnaire instrument that was analyzed thematically. Participants consisted of five students from various semesters and health study programs. The results showed that the ability to read and understand English-language medical references was the main need, followed by speaking skills in the context of professional communication. Non-formal learning media such as YouTube and TikTok were also actively utilized by students. The implications of this study indicate the importance of curriculum reformulation based on needs analysis and strengthening the English for Specific Purposes (ESP) approach in health education. These findings provide a basis for the development of teaching materials, lecturer training, and more contextual and applicable learning designs.